A study of selective precipitation techniques used to recover refined iron oxide pigments for the production of paint from a synthetic acid mine drainage solution. (April 2017) - Ryan, M.J.; Kney, A.D.; Carley, T.L.
Abstract: New resource recovery methods of acid mine drainage (AMD) treatment aim to reduce waste by extracting iron contaminants in usable forms, specifically iron oxides as industrial inorganic pigments, which can be marketed and sold to subsidize treatment costs. In this study, iron oxide pigments of varying colors and properties were recovered from a synthetic AMD solution through a stepwise selective precipitation process using oxidation, pH adjustment, and filtration. Chemical and physical design variables within the process, such as alkaline addition rate, reaction temperature, drying duration, and target pH, were altered and observed for their effects on iron oxide morphology as a means of reducing—or even eliminating—the need for refining after synthesis. Resulting iron oxide pigment powders were analyzed with X-ray diffraction (XRD) and energy dispersive spectroscopy (EDS), and visually evaluated for color and coating ability. Drying duration resulted in increased redness in paint streaks and enhanced crystallinity, as amorphous phases of iron oxide transformed into hematite. Alkaline addition rate showed no effect on the crystallinity of the powders and no consistent effect on color. Conversely, increasing reaction temperature darkened the color of pigments and increased surface area of pigment particles (thus improving coating ability) without changing the crystallinity of the samples. Iron oxides precipitated at pH 3 displayed the highest purity and possessed a distinct yellow color suggestive of jarosite, while other paint streaks darkened in color as trace metal impurities increased. The choice to use lower pH for higher quality iron oxides comes with the compromise of reduced iron recovery efficiency. Manganese and nickel did not begin to precipitate out of solution up to pH 7 and thus require increased pH neutralization in the field if natural AMD is found to contain those metals. All pigments developed in this study were found to be adequate for use as paint as demonstrated in a canvas painting. Highlights: A method for recovering iron oxide pigments from acid mine drainage is proposed. Pigments made satisfactory paint with little to no further refining after collection. Effects of chemical reactions on iron precipitation are explored. Economic recovery of iron oxides is a compromise among many factors.